Delamination localization in wind turbine blades based on adaptive time-of-flight analysis of noncontact laser ultrasonic signals. Issue 1 (2nd January 2017) - Park, Byeongjin; Sohn, Hoon; Malinowski, Pawel; Ostachowicz, Wieslaw
Abstract: In this study, a two-level scanning strategy for a noncontact laser ultrasonic measurement system is proposed to expedite the inspection of a wind turbine blade. First, coarse scanning of the entire blade is performed with a low spatial resolution for initial delamination localisation. Then, dense scanning with a high spatial resolution is performed only within the identified delaminated region for delamination visualization. This study especially focuses on the initial delamination localisation using adaptive coarse scanning. Laser ultrasonic responses from two pitch-catch paths, names inspection pairs, are obtained within a specified coarse scanning grid. Then, potential delamination locations within the given grid are estimated through time-of-flight analysis of delamination reflected waves. Once potential delamination locations are estimated, new inspection pairs are placed near the potential locations for precise localisation. These steps are repeated for every coarse scanning grids on the target wind turbine blade. The feasibility of the proposed technique for rapid delamination detection is demonstrated with a 10 kW glass fibre reinforced plastic wind turbine blade.